Pemanfaatan Aplikasi Google Maps Sebagai Upaya Branding Umkm Di Desa Kebondalem Oleh Mahasiswa Kkn-T Upn “Veteran” Jawa Timur - Dimas Oktorio Fadilla; Rafika Athiyah Kurniawan; Ida Bagus Anindya Hariwicaksana; Farrah Ayu Rashida; Putry Hafsyah Maulidinna Nurrul; Moh Heru Alfin Maulana; Mu’tasim Billah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This community service will help explain the necessary steps. Which should be followed by small bussines regarding their brand strategy and business development issues. One of the problems faced by the majority of small bussineses is the ability to promote using social media in this digitalized era. Through socialization on digital marketing, KKNT student hopes to help small bussines owners to register their bussines on Google Maps so that their bussines can be easily found by consumers and the public in general. Google Maps is an application that displays map-based location points. The purpose of this socialization is to give insight about marketing and advertising to help increase the number of customers and to be widely recognize.